VISUAL COMFORT AND USER PERCEPTION CLASSROOM LECTURE CLASSROOM ON EDUCATIONAL BUILDINGS - Muhammad Awaluddin Hamdy; Syam Fitriani Asnur (International Conference on Social and Islamic Studies, 2021)
Visual perception or human response to visual conditions that are accessed by their visual senses, is stronglyinfluenced by light because light is what allows us to access visual information. For that, it is important for usto be able to meet the need for light appropriately and in accordance with the needs of a space, both indoorand outdoor. Sunlight which is always accompanied by heat energy must be able to be maximized accordingto the needs of the space and activities in it. Lack of access to natural light, according to experts, can lead todepression and stress. Good lighting levels can be obtained from natural and artificial lighting. The use ofnatural lighting has the potential to only be in certain areas, one of the countries that has great potential isIndonesia as a country with a tropical climate that has the availability of abundant sunlight.The purpose of this study was to measure and evaluate the visual comfort of natural lighting in the classroomwhich is directly related to the building envelope and to assess the perception of room users (students) on thelevel of visual comfort. Quantitative research methods by distributing questionnaires and measurement data inthe form of tables, charts and graphs. The sample location of the study is an educational building in MakassarCity. Data analysis was carried out using correlation statistics and then simulating natural lighting in lectureclassrooms. The results of the research are expected to provide a model of a lecture classroom with naturallighting for the visual comfort of lecture classroom users.